1983
DOI: 10.1139/x83-076
|View full text |Cite
|
Sign up to set email alerts
|

Compétition pour le rayonnement solaire en début de succession secondaire dans une érablière à bouleau jaune et hêtre

Abstract: We demonstrate that sugar maple (Acersaccharum Marsh.), yellow birch (Betulaalleghaniensis Britton), and beech (Fagusgrandifolia Ehrh.) compete for solar radiation against other woody species (noncommercial) and herbaceous species, following clear-cutting. The experiment was carried out at the Duchesnay Forest Station (Quebec, Canada) in a sugar maple – yellow birch – beech community and consisted of one control and two treatments: (1) elimination of noncommercial woody species and (2) elimination of noncommer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…It is possible, however, that at higher light levels as found in clearcut areas that below-ground competition may occur. This concurs with results reported in several other studies done in the same area [3,5,6]. However, the overall lack of responsiveness of our three species contradicts many studies that have found significant effects of understory vegetation and belowground competition exclusion treatment [17,18,40,41,48,56].…”
Section: Discussionsupporting
confidence: 91%
“…It is possible, however, that at higher light levels as found in clearcut areas that below-ground competition may occur. This concurs with results reported in several other studies done in the same area [3,5,6]. However, the overall lack of responsiveness of our three species contradicts many studies that have found significant effects of understory vegetation and belowground competition exclusion treatment [17,18,40,41,48,56].…”
Section: Discussionsupporting
confidence: 91%
“…5). Bellefleur and Larocque (1983b) noted that survival was best among YB seedlings with heights greater than that of the interfering vegetation, suggesting that the critical height for YB seedlings is not absolute but relative to the interfering vegetation.…”
Section: Survivorship Of the Initial Cohort Of Yb Seedlingsmentioning
confidence: 99%
“…Etiolation clearly allowed saplings in the NC and, to some extent, in the TS treatments to exhibit similar height growth to saplings in more severe vegetation control treatments. Betula alleghaniensis' ability to preferentially invest in height versus diameter growth has previously been reported as a mechanism of response to competition for light (Bellefleur & Laroque 1983;Delagrange et al 2004), which is critical in these types of forest (Ricard et al 2003). However, maximizing height growth might be conducive to lower overall sapling vigor, especially over a prolonged period of time.…”
Section: Sapling Response To Vegetation Control Treatmentmentioning
confidence: 99%